High Prevalence of Helicobacter pylori Infection in Special Needs Schools in Japan - Kakiuchi, Toshihiko; Takamori, Ayako; Matsuo, Muneaki (Frontiers in Pediatrics, 2021)
Background: Developmental disorders and high Helicobacter pylori (H. pylori) infection rates have been pointed out. This study aimed to examine the prevalence of H. pylori in a special needs school where all students had developmental disorders in Japan. Methods: In 2017, third-grade junior high school and second- and third-grade high school students attending a special needs school with developmental disorders were enrolled. Participants of Saga Prefecture’s H. pylori test and treat project, which comprised third-grade junior high school students not from special needs school, were assigned to the control group. Results: In control group, H. pylori positive results were 3.18% (228/7,164) students. Similarly, in developmental disorder group, H. pylori positive results were 6.80% (13/191) students. For developmental disorder and control groups, this present examination sensitivity was 7.03% (13/185), specificity was 96.76% (6,815/7,043), positive predictive value was 5.39% (13/241), negative predictive value was 97.54% (6,815/6,987), Likelihood ratio of a positive result 2.17 and Odds ratio was 2.26 (95% confidence interval: 1.27–4.03, P = 0.005). Conclusion: The prevalence of H. pylori infection was significantly higher in adolescents with developmental disorders than in typically developing adolescents.